Fiber Reinforced Polymer Composites: Mechanical Properties and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Composites are the most promising material available in the twenty-first century. Composites reinforced with synthetic or natural fibers are becoming extremely prevalent as the demand for lightweight materials with high strength for specific applications grows. Fiber-reinforced polymer composite has a high strength-to-weight ratio and excellent properties, such as high durability, stiffness, damping property, flexural strength, and resistance to corrosion, wear, impact, and fire. Various properties of composite materials have led to applications in construction, aerospace, automobile, biomedical, marine, and many other industries. Because their constituent elements and manufacturing techniques primarily determine the performance of composite materials, the functional properties of various fibers available worldwide, their classifications, and the manufacturing techniques used to fabricate the composite materials must be investigated.